Permutability of proofs in intuitionistic sequent calculi - Pinto, Luís F. (1999)
We prove a folklore theorem, that two derivations in a cut-free sequent calculus for intuitionistic propositional logic (based on Kleene's {\bf G3}) are inter-permutable (using a set of basic "permutation reduction rules'' derived from Kleene's work in 1952) iff they determine the same natural deduction. The basic rules form a confluent and weakly normalising rewriting system. We refer to Schwichtenberg's proof elsewhere that a modification of this system is strongly normalising.